Situation Report: Romania, 8 December 1982 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Romanian Reaction to the Political Changes in the Kremlin New Developments Regarding Emigration Propaganda Efforts to Redefine the Concept of the Nation Saving on Electricity Foreign Students in Romania Unsportsmanlike Behavior